Role of CFT and PCR in diagnosis of Chlamydia psittaci in experimentally infected rabbits - V. V. Evstifeev; F. M. Khusainov; S. I. Yakovlev; R. I. Shangaraev; V. I. Eremets (Ветеринария сегодня)
Specific antibodies against сhlamydia weredetectedusingcomplement fixation test and сhlamydiagenome wasdetectedusingpolymerase chain reaction in pregnant rabbits experimentally infected with Chlamydiapsittaci. The infectedrabbitsdevelopeda fever andrespiratory signs andthe infection was confirmed by specificantibodiesagainst сhlamydiadetectedin theirbloodandbyabnormalities in rabbitkindling. Complement fixation testofpairedrabbit serarevealed an increasein thetitersof specificantibodiesagainst сhlamydia, which on Day 7 post infection varied within 1:7.5; on Day 14, mean concentration was 1:40 and by Day 30 mean titer increasedto 1:60. However, when pathological materials from theurogenital tractof theexperimentalanimals weretestedin polymerase chain reaction andin smear microscopy, it was impossibletoconfirm that thereisan etiological linkbetween сhlamydiaandkindlingproblems in experimental animals. At thesametime, molecularandgenetictestsof internalorgans (liver) sampledfromstillborn babyrabbitsrevealedthe сhlamydiagenome, thus, proving сhlamydia involvement into thepathological kindling. Therefore, such a retrospective methodas complement fixation test with a сhlamydia antigen is of high diagnosticvaluefor lifetime сhlamydiadiagnosis.